Ethical and Regulatory Considerations for Using Social Media Platforms to Locate and Track Research Participants. Issue 6 (3rd June 2019) - Bhatia-Lin, Ananya; Boon-Dooley, Alexandra; Roberts, Michelle K.; Pronai, Caroline; Fisher, Dylan; Parker, Lea; Engstrom, Allison; Ingraham, Leah; Darnell, Doyanne
Abstract : As social media becomes increasingly popular, human subjects researchers are able to use these platforms to locate, track, and communicate with study participants, thereby increasing participant retention and the generalizability and validity of research. The use of social media; however, raises novel ethical and regulatory issues that have received limited attention in the literature and federal regulations. We review research ethics and regulations and outline the implications for maintaining participant privacy, respecting participant autonomy, and promoting researcher transparency when using social media to locate and track participants. We offer a rubric that can be used in future studies to determine ethical and regulation-consistent use of social media platforms and illustrate the rubric using our study team's experience with Facebook. We also offer recommendations for both researchers and institutional review boards that emphasize the importance of well-described procedures for social media use as part of informed consent.